AB1177 METHODOLOGICAL ASPECTS OF DESIGN, ANALYSES AND REPORTING OF STUDIES WITH WORK PARTICIPATION AS OUTCOME DOMAIN IN PATIENTS WITH INFLAMMATORY ARTHRITIS: RESULTS OF TWO SYSTEMATIC LITERATURE REVIEWS INFORMING EULAR POINTS TO CONSIDER. (2nd June 2020) - Alunno, A.; Marques, M. L.; Boonen, A.; Falzon, L.; Ramiro, S.; Putrik, P.
Abstract : Background: Inflammatory arthritis (IA) has substantial impact on work participation (WP). However, methodological issues hamper interpretation, comparison and meta-analyses of studies with WP as outcome domain. Sources of heterogeneity and methodological choices should be assessed in order to improve the quality of future studies. Objectives: To summarize methodological choices in studies with WP as outcome domain in IA and other chronic diseases. Methods: A EULAR task force on ' points to consider (PtC) when designing, analysing and reporting studies with WP as outcome domain among patients with IA ' outlined the scope of the systematic literature review (SLR) and identified 6 areas of potential concern (Table 1 ). Two searches were conducted (Figure 1 ): Search 1 (S1): original studies in IA (RCTs and longitudinal prospective observational studies); S2: systematic reviews in other chronic diseases. Two reviewers independently identified eligible studies and extracted data for the pre-defined methodological areas. Results: We included 62 original studies in IA (23 RCTs, 16 interventional and 23 non-interventional observational studies) and 28 SLRs in other chronic diseases. The methodological aspects most often neglected in original studies (Table 1 ) were: the choice of the study design in relation to the work-related study objective; definitions of the WP outcome domains considered; accounting for skewness of the work outcome; consideration of work-related contextual factors; reporting attrition and its reasons and reporting both aggregated results as well as proportions of individuals based on predefined meaningful thresholds. SLRs on other chronic diseases confirmed high heterogeneity and methodological flaws in all the 6 key methodological areas without identifying new problematic areas. Conclusion: High methodological heterogeneity was observed in studies with WP. Consensus around the key methodological aspects is needed to homogenise and improve the quality of future studies. This review informs the EULAR PtC for the conduction and reporting of studies with WP as an outcome domain in IA. Disclosure of Interests: Alessia Alunno: None declared, Mary Lucy Marques: None declared, Annelies Boonen Grant/research support from: AbbVie, Consultant of: Galapagos, Lilly (all paid to the department), L. Falzon: None declared, Sofia Ramiro Grant/research support from: MSD, Consultant of: Abbvie, Lilly, Novartis, Sanofi Genzyme, Speakers bureau: Lilly, MSD, Novartis, Polina Putrik: None declared